Water quality impacts of the mountain pine beetle infestation in the Rocky Mountain west - McCray, John E., author; Bearup, Lindsay A., author; Rodriquez, Nicolas, author (Colorado State University. Libraries, 2014)
The Mountain Pine Beetle (MPB) is the primary cause of insect-induced mortality in pine forests in western North America where some lodgepole forests have experienced more than 90% tree mortality. The implications of MPB infestation on water resources are particularly important in the Rocky Mountains, which serve as the source-water region for more than 60 million people. Two important potential watershed impacts are changes in the hydrologic cycle and water quality. While impacts on the hydrologic cycle have received some attention, the interconnection between these changes and the impacts of the widespread infestation on water quality are not well understood. This study uses a combination of field sample analysis and modeling based in Rocky Mountain National Park to address two potential MPB-driven effects on water quality: increased metal concentrations with ecotoxicological and human health ramifications and the changes in source water contributions to streamflow with possible implications for metal and carbon transport to downstream drinking water supplies. Previous work from the research team at Colorado School of Mines identified increased potential for disinfection byproduct formation at water treatment plants receiving water from heavily MPB-killed forests. These increases exhibited surprising seasonal trends that suggest that the transport of carbon to streams, and thus the flowpaths of water, may be different in MPB-killed forests. The first question was investigated by sequentially extracting trace metals from soils under trees with vary levels of impact, and using geochemical models to identify important process-level drivers of changes in metal mobility. Laboratory results identify redistribution of metals in soils under beetle-killed trees with greater mobilization potential for cadmium, and increases in zinc and copper, likely related to fluxes from needle leachate. Results also align with geochemical models and identify changes in organic carbon inputs as the primary driver of increased metal mobility. The second questions was addressed using a chemical hydrograph separation approach to partition streamwater into the fractions derived from groundwater, rain, and snow. Results demonstrate that fractional late-summer groundwater contributions from impacted watersheds are approximately 30 ± 15% greater after infestation and when compared with a neighboring watershed that experienced earlier and less-severe attack. Water budget analysis compared to published sap flux and remotely sensing studies reveals that this change is consistent with expected increases in groundwater from loss of transpiration across the watershed. A predictive statistical model (calibrated to observations within and around Rocky Mountain National Park) suggests that dissolved organic carbon concentrations in streams will be higher in areas where tree mortality is higher. Although, a strong statistical correlation was not found with the method used. Ultimately, this study identifies process-level hydrologic and biogeochemical changes that improve understanding of the vulnerability of Rocky Mountain water supplies to MPB outbreaks.
November 2014.
Keywords: mountain pine beetle; trace metals; water quality; streamflow partitioning; Rocky Mountains